Rectal Indomethacin Does Not Mitigate the Systemic Inflammatory Response Syndrome in Acute Pancreatitis: A Randomized Trial. Issue 11 (27th November 2021) - Machicado, Jorge D.; Mounzer, Rawad; Paragomi, Pedram; Pothoulakis, Ioannis; Hart, Phil A.; Conwell, Darwin L.; de-Madaria, Enrique; Greer, Phil; Yadav, Dhiraj; Whitcomb, David C.; Lee, Peter J.; Hinton, Alice; et al.
Abstract : INTRODUCTION: Experimental data suggest that nonsteroidal antiinflammatory drugs may prevent disease severity and mortality in acute pancreatitis (AP). The aim of this study was to compare the efficacy of rectal indomethacin vs placebo in reducing the systemic inflammatory response syndrome (SIRS) score in a high-risk AP population for clinical progression. METHODS: We conducted a single-center, quadruple-blinded, randomized, placebo-controlled trial. Eligible criteria were subjects with AP and SIRS within 72 hours of presentation and those without organ failure. Subjects were allocated in a 1:1 ratio to indomethacin or placebo using simple randomization. Both interventions were administered rectally every 8 hours for 6 doses and compared using both intention-to-treat and per-protocol analyses. RESULTS: A total of 42 subjects (mean age 52 years, 55% men) were randomized to indomethacin (n = 18) or placebo (n = 24). There was no significant difference between the indomethacin and placebo groups in the change of SIRS score, proportion of subjects with SIRS, and distribution of SIRS scores at 24, 48, and 72 hours from randomization. There were no significant differences in the change of C-reactive protein levels at 48 hours or clinical outcomes between both treatment groups. Indomethacin was as safe as placebo, with 2 adverse events occurring in the placebo and none in the indomethacin arm. DISCUSSION: Rectal indomethacin can be safely administered over 48 hours; however, it is not superior to placebo in reducing the SIRS or clinical progression in a high-risk population with AP (ClinicalTrials.gov: NCT02692391).